The host immune response to gastrointestinal nematode infection in sheep - McRae, K. M. (Parasite Immunol, 2015)
Gastrointestinal nematode infection represents a major threat to the health, welfare and productivity of sheep populations worldwide. Infected lambs have a reduced ability to absorb nutrients from the gastrointestinal tract, resulting in morbidity and occasional mortality. The current chemo‐dominant approach to nematode control is considered unsustainable due to the increasing incidence of anthelmintic resistance. In addition, there is growing consumer demand for food products from animals not subjected to chemical treatment. Future mechanisms of nematode control must rely on alternative, sustainable strategies such as vaccination or selective breeding of resistant animals. Such strategies take advantage of the host's natural immune response to nematodes. The ability to resist gastrointestinal nematode infection is considered to be dependent on the development of a protective acquired immune response, although the precise immune mechanisms involved in initiating this process remain to be fully elucidated. In this study, current knowledge on the innate and acquired host immune response to gastrointestinal nematode infection in sheep and the development of immunity is reviewed.